An Overview of the Mechanisms of Plant Ingredients in the Treatment of Diabetes Mellitus - SZ Bathaie; N Mokarizade; S Shirali (Institue of Medicinal Plants, ACECR, 2012)
Diabetes has no cure, but complementary therapy being used to reduce its complications. Medicinal plants have been applied to control the blood glucose reducing the diabetic complications, increasing the life span and quality of life in these patients. The purpose of this study is investigating the active compounds of these medicinal plants and their mechanisms of action. Up to now, over 1200 species in 725 genera and 183 families of herbals have been reported with antidiabetic activity. We also reported the therapeutic effects of saffron extract and crocin, as one of its purified components, in both in vivo and in vitro conditions. To classify the medicinal plants according to their active compound and mechanism of action, all databases, especially Web of Science and PUBMED with different keywords like "Medicinal plant, Antidiabetic component, Mechanism of action, etc.," without restrictions in the year was conducted. Then, based on the active ingredient of plant material and the mechanism of action of these materials, the articles were classified. Results showed nine main groups of materials: Imidazolines, Alpha - Lipoic Acid, Phenylpropanoids (including flavonoids, Stilbenoids and lignins), phenolic acids, saponins, alkaloids, polysaccharides, amino acids, carotenoids and dietary fibers, alone or mixed, as the antidiabetic components. Overall, one or several of these activities are found in these materials: stimulating insulin secretion, antioxidant property, inhibition or activation of some enzymes, alteration in the expression of genes involved in the glucose catabolism or excretion, and inhibition of sugar binding to the biomacromolecules such as proteins and DNA.